Mystique versus Machismo: Sex Differences in HIV Infection - Eileen P. Scully (Case Western Reserve University, 2018)
Biological sex is a determinant of both susceptibility to and pathogenesis of multiple infections, including HIV. These differences have effects on the spectrum of HIV disease from acquisition to eradication, with diverse mechanisms including distinct chromosomal complements, variation in microbiota composition, hormonal effects on transcriptional profiles, and expression of different immunoregulatory elements. With a comparative biology approach, these sex differences can be used to highlight protective and detrimental immune activation pathways, to identify strategies for effective prevention, treatment, and curative interventions.